2009
DOI: 10.1080/00016340902998436
|View full text |Cite
|
Sign up to set email alerts
|

Women's fear of childbirth and preference for cesarean section – a cross‐sectional study at various stages of pregnancy in Sweden

Abstract: When a woman requests a cesarean section, both primary fear of birth and traumatic childbirth experiences need to be considered and dealt with. The W-DEQ can be used at any time during pregnancy in order to identify pregnant women who suffer from intense fear of childbirth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
273
7
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 309 publications
(323 citation statements)
references
References 26 publications
17
273
7
11
Order By: Relevance
“…The finding that 6.2% of unselected pregnant women stated a preference for CS is low but comparable to previous Scandinavian research [22,24,[26][27]. According to a review that included 38 studies worldwide (including few Asian and African studies), the overall pooled preference was 15.6% [28], with the highest rates in the Americas.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The finding that 6.2% of unselected pregnant women stated a preference for CS is low but comparable to previous Scandinavian research [22,24,[26][27]. According to a review that included 38 studies worldwide (including few Asian and African studies), the overall pooled preference was 15.6% [28], with the highest rates in the Americas.…”
Section: Discussionsupporting
confidence: 77%
“…Questionnaire (W-DEQ), Version A [22]. The W-DEQ is a 6-point, 33-item self-assessment rating scale with a minimum score of 0 and a maximum of 165.…”
Section: Fear Of Childbirth Was Assessed By the Wijma Delivery Expectmentioning
confidence: 99%
See 1 more Smart Citation
“…Intense fear of childbirth occurs in 7 to 26 percent of pregnant women (Fenwick, Gamble, Nathan, Bayes, & Hauck, 2009;Laursen, Johansen, & Hedegaard, 2009), with a smaller proportion developing extreme fear or tokophobia (Nieminen, Stephansson, & Ryding, 2009). The BIDENS study of 7,200 women in six European countries found significant differences between countries with prevalence ranging from 1.9 to 14.2% (Van Parys, Ryding, Schei, Lukasse, & Temmerman, 2012).…”
Section: Fear Of Childbirthmentioning
confidence: 99%
“…There is good evidence from large epidemiological studies that women with fear of childbirth are more likely to want interventions such as epidural analgesia and caesarean sections (Nieminen et al, 2009;Rouhe et al, 2009). Evidence on the relationship between fear of childbirth and birth outcomes is inconsistent, however the balance of evidence suggests fear of birth is associated with negative outcomes such as increased labour duration (Adams, Eberhard-Gran, & Eskild, 2012) and caesarean section (Laursen et al, 2009;Sydsjo et al, 2013;Waldenstrom, Hildingsson, & Ryding, 2006).…”
Section: Fear Of Childbirthmentioning
confidence: 99%